Analysis of Implementation of Guidance and Counseling Post Pandemic Covid 19 as a Basis for Service Development: High Schools, Vocational High Schools and Madrasah Aliyah - Hartini, Hartini (Konseling Edukasi : Journal of Guidance and Counseling, 2023)
Analysis of Implementation of Guidance and Counseling Post Pandemic Covid 19 as a Basis for Service Development: High Schools, Vocational High Schools and Madrasah Aliyah. The aim of the research is to analyze the implementation of post-pandemic covid 19 guidance and counseling services in senior high schools, vocational schools and Islamic high schools. The research method uses a quantitative survey method approach. The research subjects were 72 high school students. Random sampling technique. The instrument used was in the form of a questionnaire which totaled 29 questions packaged in a google form. The questionnaire was tested for legibility and validity with the acquisition of an r count of 0.635 > R table0.2126. Data analysis using percentages. The results of the study found that the implementation of post-Covid 19 Guidance and Counseling services was utilized by students through guidance and counseling teachers. However, problem solving is only felt by some students because solutions are still in the form of advice and punishment, the majority of services are carried out online using whatshap and zoom/google meet and are focused on responsive services, namely individual counseling and group guidance, the field of tutoring is more dominantly carried out, so it becomes a record for Vocational High School teachers to provide more career guidance.  Research findings can become the basis for developing advanced services and considering related parties so that guidance and counseling services can be fully integrated and in achieving educational goals Keywords: Guidance and counseling services; Post covid 19; High Schools, Vocational High Schools and Madrasah Aliyah